2005
DOI: 10.1007/s00701-005-0663-7
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical considerations of the anterior spinal and the anterior-ventral spinal arteries

Abstract: This anatomical study gives important information for a better understanding of the clinical picture of ischemic lesions of the brain stem, such as the medial medullary syndrome, and highlights the remarkable role of the AVSA and ASA as anatomical landmarks during the surgical approaches to lesions involving the ventral aspect of the medulla and the foramen magnum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…11 In fact in another human cadaver series the 'typical' bilateral origin of the anterior spinal artery was the least common variant. 12 Therefore, the mechanism and location of the stroke in our case can be explained by either thrombotic occlusion of a lone unilateral right anterior spinal artery where it arises from the right vertebral artery, or by an occlusion of a small penetrating artery by an embolus from the atherosclerotic right vertebral artery.…”
mentioning
confidence: 72%
“…11 In fact in another human cadaver series the 'typical' bilateral origin of the anterior spinal artery was the least common variant. 12 Therefore, the mechanism and location of the stroke in our case can be explained by either thrombotic occlusion of a lone unilateral right anterior spinal artery where it arises from the right vertebral artery, or by an occlusion of a small penetrating artery by an embolus from the atherosclerotic right vertebral artery.…”
mentioning
confidence: 72%
“…High anatomical variability of the ASA origin exists, and it often has either a predominance of one ramus over the other or a sole unilateral ramus of origin ( 11 , 12 ). The Santos-Franco et al study reported a less typical bilateral origin of the ASA ( 13 ).…”
Section: Cervical Asa Anatomymentioning
confidence: 95%
“…La AB presenta evidentes variaciones en su expresión morfológica relacionadas con su origen, longitud, trayectoria y calibre (Torche et al, 1992;Akar et al, 1994;Schulte-Altedorneburg et al, 2000;Mandiola et al, 2004;Pai et al, 2007;Songur et al, 2008). Además del surco pontomedular, esta puede originarse por debajo o por arriba de este surco referente (Stopford, 1916;Wojtowicz et al, 1989;Santos-Franco et al, 2006;Stopforf;Songur et al).…”
Section: Introductionunclassified
“…Las variaciones de la AB no determinan per se, diferencias en el suministro de sangre en los territorios irrigados, pero las variaciones sumadas a otros factores como estenosis, ateromatosis, embolia o trombosis son causa de cuadros clínicos originados en el tallo cerebral (Wollschlaeger et al, 1967;Schulte-Altedorneburg et al;Pico et al, 2006;Deng et al, 2012). Las expresiones morfológicas de la AB han sido descritas mediante técnicas de disección clásica, inyección de sus lechos vasculares o estudios imagenológicos en otros grupos poblacionales (Stopford;Smoker et al,;Mandiola et al, 1995;Pai et al;Santos-Franco et al;Wojtowicz et al). Con el propósito de obtener información propia de referencia, este estudio contó con muestras cadavéricas frescas de sujetos colombianos.…”
Section: Introductionunclassified